PIF4‐induced BR synthesis is critical to diurnal and thermomorphogenic growth. (2nd November 2018) - Martínez, Cristina; Espinosa‐Ruíz, Ana; de Lucas, Miguel; Bernardo‐García, Stella; Franco‐Zorrilla, José M; Prat, Salomé
Abstract: The Arabidopsis PIF4 and BES1/BZR1 transcription factors antagonize light signaling by facilitating co‐activated expression of a large number of cell wall‐loosening and auxin‐related genes. While PIF4 directly activates expression of these targets, BES1 and BZR1 activity switch from a repressive to an activator function, depending on interaction with TOPLESS and other families of regulators including PIFs. However, the complexity of this regulation and its role in diurnal control of plant growth and brassinosteroid (BR) levels is little understood. We show by using a protein array that BES1, PIF4, and the BES1‐PIF4 complex recognize different DNA elements, thus revealing a distinctive cis‐regulatory code beneath BES1‐repressive and PIF4 co‐activation function. BES1 homodimers bind to conserved BRRE‐ and G‐box elements in the BR biosynthetic promoters and inhibit their expression during the day, while elevated PIF4 competes for BES1 homodimer formation, resulting in de‐repressed BR biosynthesis at dawn and in response to warmth. Our findings demonstrate a central role of PIF4 in BR synthesis activation, increased BR levels being essential to thermomorphogenic hypocotyl growth. Synopsis: Plant elongation in response to warmth and light is tightly controlled by steroid hormone‐sensitive gene expression, but the dynamic regulation of this circuitry remains unresolved. Here, crosstalk between the Arabidopsis transcription factors PIF4 and BES1 is shown to activate brassinosteroid (BR) synthesis and adjust seed stem growth to the daily changes of environmental stimuli. Interaction with PIF4 switches BES1 activity from a repressive to an activator function. BES1 binds as a homodimer to conserved BRRE and G‐box elements in the promoters of BR biosynthetic and BES‐DOWN genes. The PIF4‐BES1 complex recognizes a CATGTG motif or PBE‐element that is enriched in the promoters of PIF‐UP and PIF + BES‐UP targets. Accumulation of PIF4 at warm temperatures up‐regulates BR levels by competing for BES1 homodimerization. Abstract : The transcription factor PIF4 confers adaptation of plant hormone activation during warmth‐dependent hypocotyl growth.